Communications, Signal Processing, and Systems Proceedings of the 2017 International Conference on Communications, Signal Processing, and Systems - Liang, Qilian; Mu, Jiasong; Jia, Min; Wang, Wei; Feng, Xuhong; Zhang, Baoju (Lecture Notes in Electrical Engineering,, 2019)
This book brings together papers presented at the 2017 International Conference on Communications, Signal Processing, and Systems (ICCSP 2017), which was held on July 14-17, 2017 in Harbin, China. Presenting the latest developments and discussing the interactions and links between these multidisciplinary fields, the book spans topics ranging from communications, signal processing and systems. It is aimed at undergraduate and graduate electrical engineering, computer science and mathematics students, researchers and engineers from academia and industry as well as government employees.